ANALISIS PERLINDUNGAN HAK ANAK PADA KASUS PENGASUHAN KINSHIP CARE BERDASARKAN TEORI JUSTICE DI SEMAMPIR SURABAYA - Vanessa Amalia; Olivia Afriska Ramadhani; Muhammad Al-Mutashim Billah (Islamic Family Law, STAI Sangatta Kutai Timur, 2025)
Kinship care constitutes an important alternative form of childcare when biological parents are unable to provide adequate protection and meet their children’s needs due to factors such as divorce, poverty, or death. In the Semampir area of Surabaya, kinship care is widely practiced; however, the fulfillment of children’s rights remains suboptimal. Many children living under kinship care arrangements experience unequal access to education, healthcare services, psychological support, and adequate housing, while also facing social stigma that exacerbates both their vulnerability and the burden placed on caregivers. This study examines the protection of children’s rights within the context of kinship care through the lens of John Rawls’s theory of distributive justice. Employing an empirical socio-legal method, data were collected through in-depth interviews, participatory observation, and documentation analysis of divorce-related cases. The findings reveal that economic constraints, social discrimination, and weak legal support mechanisms contribute to the unequal distribution of resources and inadequate protection afforded to children in kinship care settings. The study concludes that the application of social justice principles is essential to strengthening child protection mechanisms and ensuring the fair and equitable fulfillment of children’s rights. Accordingly, policy interventions should actively involve the government, social institutions, and community actors to create an integrated and justice-oriented kinship care framework.